Indicators of Migrants Socio-Professional Integration - Emilio Gregori (Fondazione Eni Enrico Mattei (FEEM), 2006)
Understanding and monitoring the diversity which lies under migrants socio-professional integration trends is a challenge that both Governments and local administrations must be able to face. This paper is about a research project, developed under the EU initiative Equal, consisting in the establishment of a set of indicators of professional and social integration of migrant people in Italy, based on data collected from administrative and official sources. This work was carried out starting from a literature analysis of both theoretical and empirical experiences in the Italian context. The problem of the theoretical concept of migrants, foreigners and integration was discussed, as well as the matters concerning the dimensions of professional integration, the reliability of sources, the methodology, the operating definition of indicators and above all the correct interpretation of quantitative results, from the point of view of the level of integration. The set of indicators was empirically implemented for a first validation at a national, regional and local level, building annual time series from 1996 to 2001. Studying socio-economic migrants integration is a key challenge in order to offer tools for the implementation of policies able to promote equal opportunities of access and mobility in the labour market. Active policy promotion, i.e. the support of foreign people in the acquisition of the basic linguistic skills and in lifelong-learning, is a useful way not only to promote occupation but also to prevent discrimination problems in the workplace: the correct implementation of these policies is possible only if based on multidimensional analysis of migrants placement in the labour market.
Keywords: J15; 330; Indicators; Migrants; Integration; Soziale Integration; Italien; Berufliche Integration; Migranten